Асимптотична поведінка розв’язку лінійних стохастичних диференціально-різницевих рівнянь нейтрального типу - Царков, Є.Ф.; Малик, І.В. (Видавничий дім "Академперіодика" НАН України, 2008)
Necessary and sufficient conditions of the mean square exponential stability of a linear stochastic differential-difference equation of neutral type in the scalar case are obtained.